2015
DOI: 10.3389/fpls.2015.00871
|View full text |Cite
|
Sign up to set email alerts
|

Temporal analysis reveals a key role for VTE5 in vitamin E biosynthesis in olive fruit during on-tree development

Abstract: The aim of this work was to generate a high resolution temporal mapping of the biosynthetic pathway of vitamin E in olive fruit (Olea europaea cv. “Koroneiki”) during 17 successive on-tree developmental stages. Fruit material was collected from the middle of June until the end of January, corresponding to 6–38 weeks after flowering (WAF). Results revealed a variable gene regulation pattern among 6–38 WAF studied and more pronounced levels of differential regulation of gene expression for the first and intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 37 publications
6
33
1
Order By: Relevance
“…Our results showed that the α-tocopherol content of the Ayvalık cultivar was between 26.78 and 21.05 mg/100 g, with the highest levels noted for the 21 October samples. The results from the Koroneiki cultivar revealed similar values within the same stages of maturation (Georgiadou et al, 2015). Both cultivars exhibited increased α-tocopherol content at early stages of maturation.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Our results showed that the α-tocopherol content of the Ayvalık cultivar was between 26.78 and 21.05 mg/100 g, with the highest levels noted for the 21 October samples. The results from the Koroneiki cultivar revealed similar values within the same stages of maturation (Georgiadou et al, 2015). Both cultivars exhibited increased α-tocopherol content at early stages of maturation.…”
Section: Discussionsupporting
confidence: 63%
“…Although it is known that ethylene levels increase throughout the fruit ripening process (Lelievre et al, 1997), tocopherol levels exhibit different patterns in different olive cultivars. Although Hojiblanca (Beltran et al, 2005) and Koroneiki (Georgiadou et al, 2015) exhibited an increase, Verdial and Villalonga (Garcia et al, 1996) exhibited a decrease in α-tocopherol content. In addition, the arbequina and lechin (Garcia et al, 1996) cultivars did not exhibit significant changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, increasing the tocopherol content could be an auto-protection mechanism of plants against some stress conditions, such as water stress (Beltrán et al, 2010). However, there is a maximum level depending on the fruit development (Georgiadou et al, 2015). In this line, our results show that climate factors are linked to tocopherols content and may impact them, but the influence of other factors providing synergic or antagonist effects, as the maturation index, cannot be discarded.…”
Section: Tocopherolsmentioning
confidence: 61%